FRI0397 Baseline characteristics of systemic sclerosis patients with borderline mean pulmonary artery pressure: post-hoc analysis from the detect study. (23rd January 2014) - Khanna, D.; Distler, O.; Coghlan, J. G.; Denton, C. P.; Grünig, E.; Bonderman, D.; Müller-Ladner, U.; Pope, J. E.; Vonk, M. C.; Torres-Martin, J.-V.; Doelberg, M.; Chadha-Boreham, H.; et al.
Abstract : Background: Patients with mean pulmonary artery pressures (mPAP) of 21–24 mmHg have 'borderline' pulmonary arterial hypertension (PAH) and may represent an early, milder stage of pulmonary vasculopathy in those at high risk of PAH. 1 Case detection strategies would facilitate investigation of natural history and the value of intervention. Objectives: Post-hoc analysis of systemic sclerosis (SSc) patients from the DETECT study to examine baseline characteristics of those with normal mPAP, borderline PAH (boPAP), and PAH. Methods: DETECT was a multicentre cross-sectional study conducted to develop an evidence-based tool for detecting PAH in SSc patients to limit missed PAH diagnoses. Adults with SSc for >3 years, a DLCO <60% of predicted, and no previous diagnosis of pulmonary hypertension underwent accessible screening tests followed by diagnostic right heart catheterisation (RHC). Patients included in the current analysis had a PCWP ≤15 mmHg and no significant interstitial lung disease. We applied the following definitions: normal=mPAP <21 mmHg; boPAP=mPAP ≥21–24 mmHg; PAH=mPAP ≥25 mmHg. Variables were selected based on numerical descriptive differences between the 3 groups and on published clinical information and were compared using non-parametric tests. Univariable logistic regression assessed the strength of association with boPAP vs normal mPAP (odds ratio [OR]). P<0.05 was statistically significant. Results: Of 466 SSc patients, 187 had normal mPAP, 57 boPAP, and 87 PAH. Differences in baseline characteristics are given in the table x. In univariable analyses (normal vs boPAP), older age (OR 1.03), peripheral oedema (OR 5.12), greater left atrium size (OR 1.12), greater right atrial area (OR 1.08), greater TR velocity (OR 2.99), higher mean PCWP (OR 1.34), and higher PVR (OR 1.01) were statistically significant and associated with boPAP. Conclusions: In this post-hoc analysis, older age, peripheral oedema, echocardiographic findings, and individual RHC parameters were able to distinguish SSc patients with normal mPAP from those with boPAP. Guided by clinical suspicion, RHC remains the crucial diagnostic procedure. References: Bae S et al. Ann Rheum Dis 2012;71:1335–42. Disclosure of Interest : D. Khanna Grant/research support from: Actelion, BMS, Gilead, Genentech, ISDIN, United Therapeutics, Consultant for: Actelion, BMS, Gilead, Genentech, ISDIN, United Therapeutics, Bayer, Sanofi-Aventis, Merck, Roche, Speakers bureau: Actelion, United Therapeutics, O. Distler Grant/research support from: Actelion, Pfizer, Ergonex, Sanofi-Aventis, Consultant for: Actelion, Pfizer, Boehringer-Ingelheim, Bayer, Roche, Ergonex, BMS, Sanofi-Aventis, United Biosource Corporation, Medac, Biovitrium, Novartis, Active Biotech, 4D Science, Sinoxa, Speakers bureau: Actelion, Pfizer, Ergonex, J. Coghlan Grant/research support from: Actelion, Pfizer, GSK, United Therapeutics, Consultant for: Actelion, Pfizer, GSK, United Therapeutics, Speakers bureau: Actelion, Pfizer, GSK, United Therapeutics, C. Denton Grant/research support from: Actelion Pharmaceuticals Ltd, Pfizer, GSK, Sanofi-Aventis, and Novartis, Consultant for: Actelion Pharmaceuticals Ltd, Pfizer, GSK, Sanofi-Aventis, and Novartis, Speakers bureau: Actelion Pharmaceuticals Ltd, Pfizer, GSK, Sanofi-Aventis, and Novartis, E. Grünig Grant/research support from: Actelion, Bayer, GSK, Encysive, Lilly, Pfizer, Consultant for: Actelion, Bayer, Gilead, GSK, Lilly, Milteney, Novartis, Pfizer, Rotex Medica, Speakers bureau: Actelion, Bayer, Gilead, GSK, Lilly, Milteney, Novartis, Pfizer, Rotex Medica, D. Bonderman Grant/research support from: Actelion, Consultant for: Actelion, U. Müller-Ladner Grant/research support from: Actelion, Consultant for: Actelion, Speakers bureau: Actelion, Pfizer, GSK, J. Pope Grant/research support from: Actelion, Amgen, Abbott, BMS, UCB, Janssen, Roche, Celgene, Consultant for: Actelion, Amgen, Abbott, BMS, Pfizer, UCB, Janssen, Roche, GSK, Speakers bureau: Amgen, BMS, Pfizer, M. Vonk Grant/research support from: Actelion, Pfizer, GSK, United Therapeutics, Therabel Pharma, Consultant for: Actelion, Pfizer, Speakers bureau: Actelion, Pfizer, J.-V. Torres-Martin Employee of: Actelion, M. Doelberg Shareholder of: Actelion, Employee of: Actelion, H. Chadha-Boreham Shareholder of: Actelion, Employee of: Actelion, H. Heinzl Grant/research support from: Roche Austria, Consultant for: Actelion, D. Rosenberg Shareholder of: Actelion, Employee of: Actelion, V. McLaughlin Grant/research support from: Actelion, Bayer, Novartis, United Therapeutics, Consultant for: Actelion, Bayer, Gilead, United Therapeutics, Speakers bureau: Actelion, Gilead, United Therapeutics, J. Seibold Grant/research support from: Actelion, Gilead, United Therapeutics, Consultant for: Actelion, Pfizer, Gilead, United Therapeutics, Boehringer-Ingelheim, Bayer, Sigma Tau, FibroGen, Sanofi-Aventis, Celgene, MedImmune, Genentech, InterMune